2006
DOI: 10.1007/s11255-006-9152-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral honey application for urethral injury: an experimental study

Abstract: Intraurethral honey, applied after urethral injury, prevents inflammation, accelerates urethral healing and provides perfect healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Honey is easy to apply, helpful in cleaning the wounds, and without side effects Reduces pain [66,84,92] Molan [63] published a review article that covered the various reports that have been published on the clinical usage of honey. Positive findings on honey in wound care have been reported from 17 randomized controlled trials (1965 patients) and five clinical trials of other forms (97 patients) treated with honey.…”
Section: Type Of Lesion Effects Of Honeymentioning
confidence: 99%
See 2 more Smart Citations
“…Honey is easy to apply, helpful in cleaning the wounds, and without side effects Reduces pain [66,84,92] Molan [63] published a review article that covered the various reports that have been published on the clinical usage of honey. Positive findings on honey in wound care have been reported from 17 randomized controlled trials (1965 patients) and five clinical trials of other forms (97 patients) treated with honey.…”
Section: Type Of Lesion Effects Of Honeymentioning
confidence: 99%
“…Another study was performed to evaluate the effect of honey applied intraurethrally after urethral injury on histopathological healing in male rats. Results showed that intraurethral honey, applied after urethral injury, prevents inflammation and accelerates urethral healing [66]. A study has shown that intraperitoneal honey administration reduces postoperative peritoneal adhesion; the wound healing accelerative effect and the mechanical barrier formed by the honey was explained to be the reasons for its inhibitory effect on the adhesion [44].…”
Section: Type Of Lesion Effects Of Honeymentioning
confidence: 99%
See 1 more Smart Citation
“…Daily application of a lubricating honey solution caused an improvement in urethral coverage, healing and narrowing after 21 days [ 27 ]. The use of dexpanthenol as catheter lubricant caused a decrease in urethral fibrosis in case of high dose treatment and a decrease in inflammation in both low and high dosage groups [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rats were anaesthetized with a combination of ketamine-xylazine intraperitoneally before experiment. Urethral injury was created with the method previously described by Ayyıldız et al (10). The control group was not intervened.…”
Section: Creation Of Urethral Injury In Rats and Materials Collectionmentioning
confidence: 99%